Ultrasound-mediated gene delivery of factor VIII plasmids for hemophilia A gene therapy in mice - Shuxian Song; Meghan J. Lyle; Misty L. Noble-Vranish; Dominic M. Min-Tran; James Harrang; Weidong Xiao; Evan C. Unger; Carol H. Miao (Elsevier, 2022)
Gene therapy offers great promises for a cure of hemophilia A resulting from factor VIII (FVIII) gene deficiency. We have developed and optimized a non-viral ultrasound-mediated gene delivery (UMGD) strategy. UMGD of reporter plasmids targeting mice livers achieved high levels of transgene expression predominantly in hepatocytes. Following UMGD of a plasmid encoding human FVIII driven by a hepatocyte-specific promoter/enhancer (pHP-hF8/N6) into the livers of hemophilia A mice, a partial phenotypic correction was achieved in treated mice. In order to achieve persistent and therapeutic FVIII gene expression, we adopted a plasmid (pHP-hF8-X10) encoding an FVIII variant with significantly increased FVIII secretion. By employing an optimized pulse-train ultrasound condition and immunomodulation, the treated hemophilia A mice achieved 25%-150% of FVIII gene expression on days 1-7 with very mild transient liver damage, as indicated by a small increase of transaminase levels that returned to normal within 3 days. Therapeutic levels of FVIII can be maintained persistently without the generation of inhibitors in mice. These results indicate that UMGD can significantly enhance the efficiency of plasmid DNA transfer into the liver. They also demonstrate the potential of this novel technology to safely and effectively treat hemophilia A.